EXPERIMENTAL INVESTIGATION ON CASCADED MULTILEVEL INVERTER USING SINGLE VOLTAGE SOURCE TOPOLOGY (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This paper presents a cascaded H-bridge multilevel inverter with single DC source. Generally, each phase of the multilevel inverter requires ‘n’ number of DC sources for 2n+1 level. In this paper we have proposed a multilevel topology which requires only one DC source for all the three phases and other sources are replaced by ultra capacitors. Initially, the performance of multi level inverter has been studied by including all DC sources. Finally a single DC source is allowed and remaining n-1 DC sources are replaced by ultra capacitors. An adaptive PI controller is introduced for automatically maintaining the voltage level of capacitor and we use higher number of output levels to increase the quality of power. Comparison between both the cascaded multilevel inverter using DC source and ultracapacitor as source has been studied and it shows that the overall performance of ultracapacitor source is better than that of DC source. An experiment has been performed and the result shows that the proposed system is suitable for medium power applications.